Pengaruh Electronic Word of Mouth, Web Quality, Online Costumer Review, dan Reputasi Terhadap Keputusan Pembelian Situs Online Tokopedia di Malang - Amanda, Nina Septira Putri; Rizal, Mohammad; Arsyianto, Muhammad Tody (E-JRM : Elektronik Jurnal Riset Manajemen, 2025)
Abstract The result  show that the influence of  Web quality reputation variables is very significant, consumers believe that website quality can affect consumers and potential consumers to continue transacting and make it easier to buy, reputation is also very influental because with the image, consumers believe that this store or online site is guaranteed in terms of quality and quantity, in contrast to the Electronic Word of Mouth and Online Costumer Review variables, consumers are less confident because there is   no real evidence, only  reviews from consumers who have bought and given bad reviewa are presented. Keywords:  Electronic Word Of Mouth, Reputation,  Tokopedia,  Web Quality, Online Costumer